Olga Markova. Axiological component of the patriotism concept on material of the ukrainian newspaper discourse - Olga Markova (Philological Treatises, 2020)
An axiological component contained in the PATRIOTISM concept is discovered through the texts of the Ukrainian media, it is represented by the vocabulary, which reflects the peculiarities of the Ukrainian people’s mentality, worldview and life values. The linguistic units form the subjective and figurative loading of the axiological content of this concept. They are endowed with universal as well as specific national characteristics: the system of people’s views on the society; love for everything native (language, culture, traditions, etc.), which is inherited and cultivated in the people; revealing a sense of love and responsibility for the fate of their people when social interests are preferred over their own. Since an axiological component reveals the degree of significance of the perceived content for the subject, the following features are distinguished in the study: scale (within the family, city, and country), the presence of the past (respect for the traditions), present and future (patriotism as a pledge of a happy, independent, developed country), activity or passivity in the external environment. The subjective and estimative attitude of a person to the phenomenon of PATRIOTISM has been revealed.